Membangun Ketahanan Rantai Pasokan Maritim: Peran Strategis Manajemen Pelabuhan dalam Menghadapi Gangguan Logistik dan Disrupsi Perdagangan Internasional - Laurenz, Omega Trifena (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research explores the strategic role of port management in building maritime supply chain resilience, especially in the context of logistics disruption and international trade disruption. As complexity and volatility in global trade increases, ports around the world face significant challenges in maintaining efficient and reliable operations. This study highlights the importance of technological innovation, adaptive policies and inter-stakeholder collaboration as key elements in improving maritime supply chain resilience. Through case analysis and literature review, this research identifies best practices in port management that can be applied to reduce the impact of logistics disruptions, such as natural disasters, economic crises, and global pandemics. Apart from that, this research also emphasizes the need for the integration of sophisticated information systems and the development of strong infrastructure to support the continuity of port operations. Thus, this research provides valuable insights for stakeholders in the maritime industry, including governments, port operators, and logistics companies, to develop effective strategies to face future challenges.